2019
DOI: 10.1111/padm.12575
|View full text |Cite
|
Sign up to set email alerts
|

Good to share? The pecuniary implications of moving to shared service production for local government services

Abstract: Shared services are often lauded as an efficacious means of reducing municipal expenditure and thereby improving waning financial sustainability. However, most of the extant theoretical and empirical work only considers costs and benefits at the level of the specific service in question and, hence, fails to capture many of the wider benefits and costs that might accrue to local governments. In this article we first build a schema to illustrate the benefits and costs of moving from separate to collaborative pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…While these findings provide support for structural reform in the São Paulo local government system, it is critical to consider the role that shared services may play in curbing municipal expenditure. It should be noted there is considerable evidence among developed nations that inter-municipal collaboration through shared service arrangements may represent a potentially fruitful avenue of reform (e.g., Tomkinson, 2007;Dollery et al, 2012) although more recent evidence suggests that shared services may result in reduced technical efficiency (Drew et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While these findings provide support for structural reform in the São Paulo local government system, it is critical to consider the role that shared services may play in curbing municipal expenditure. It should be noted there is considerable evidence among developed nations that inter-municipal collaboration through shared service arrangements may represent a potentially fruitful avenue of reform (e.g., Tomkinson, 2007;Dollery et al, 2012) although more recent evidence suggests that shared services may result in reduced technical efficiency (Drew et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tables 5 and 6 present the regressions estimating the relationship between sharing a SMT and public service efficiency and effectiveness. Following McQuestin and Drew, McQuestin, and Dollery (2019), we report estimates controlling for a linear (models 1 and 3) and a nonlinear (models 2 and 4) population-performance relationship. To estimate the nonlinear relationship, a squared version of the population variable was added to the models.…”
Section: Organizational Performance Effects Of Shared Smtsmentioning
confidence: 99%
“…Research suggests that inter‐local co‐operation has grown considerably in the United States (US) and many other countries during the past thirty years (Kwon and Feiock 2010; Bel, Mildred, and Warner 2015). In particular, empirical studies have identified a movement toward the sharing of services, such as IT, HR, and procurement, in the United States (Henderson 2014), Australia (Drew, McQuestin, and Dollery 2019), England (Dixon and Elston 2020), and Germany (Niehaves and Krause 2010). However, to date, little systematic empirical analysis has addressed the reasons for appointing a single SMT to run all of the services provided by separate local governments 2…”
Section: Antecedents Of Shared Senior Management Teamsmentioning
confidence: 99%
“…Special districts are governments tasked with a specific function and have the legal ability to raise revenue to complete that function (Mullin, 2009). Having a higher number of special districts in an area offloads responsibility for public services from other local governments and reduces their financial burden (Drew et al, 2019). This assumption leads to the second hypothesis:H2 : The more special districts in a county, the less that county will utilize property tax revenue .…”
Section: Explanations For Underutilization Of Property Tax Revenuementioning
confidence: 99%